Is a Policy of Free Movement of Workers Sustainable? - Pierre M. Picard; Tim Worrall (Institute for the Study of Labor (IZA), 2014)
This paper studies the costs and benefits of the adoption of the policy of free movement for workers. For the countries to agree on uncontrolled movement of workers, the short run costs must be outweighed by the long term benefits that result from better labor market flexibility and income smoothing. We show that such policies are less likely to be adopted when workers are impatient and less risk averse workers, when production technologies display decreasing returns and when countries trade a share of their products.
Keywords: F22; J61; 330; labor market flexibility; migration; sustainable plan